THE EFFECT OF COMPRESSOR WASH ON GAS TURBINE TEMPERATURE OF TURBOFAN ENGINE - Abubakar, Abubakar; Wijayanti , Widya (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
In this study, the impact of compressor washing on improving the performance and engine life of a turbofan engine is analyzed. The purpose of this research is to determine the outcomes resulting from the compressor wash treatment, as well as the patterns and characteristics of engine deterioration rates in each block cycle following the wash. It also aims to identify the optimal timing for conducting a compressor wash to achieve the most favorable results and maximize the on-wing life of the engine. This research was conducted using an analytical method, which involved analyzing the data received from the Aircraft Communications Addressing and Reporting System (ACARS) to assess the influence of engine performance and deterioration characteristics on the conducted compressor wash. One set of temperature margin data analyzed reveals the benefits of washing in terms of the turbine gas temperature (TGT) margin. It shows a 7°C increase in the TGT margin, indicating improved performance, but a 3.1°C decrease in the unrecoverable margin. Furthermore, the analysis of the margin data per 100 cycles indicates that the rate of deterioration is steeper during the initial 300 cycles compared to the subsequent cycles. Based on these findings, it is recommended to conduct the compressor washing process at around 300 cycles to maximize engine life and achieve enhanced efficiency.